THE RELATIONSHIP BETWEEN A LEVEL OF UTILIZATION OF AI CHAT GPT AS THE LEARNING MEDIUM AND THE PROVISIONAL ACHIEVEMENT INDEX (IPS) OF PAI UINSA STUDENTS IN SEMESTER 5 - Abadiyah, Rosyida; Multazami, M; Maulidiyah, Hidayatul; Kurnia Alviatin, Anis; Hidayatullah, Muhammad Rizqi; Rahman, Fathur (Jurnal Inovasi dan Teknologi Pendidikan, 2026)
The development of artificial intelligence (AI) technology is increasingly influencing the learning process, including in higher education. One AI technology that is widely used by students is ChatGPT, a deep learning-based language model that is capable of providing information, explanations, and feedback quickly and interactively. This study aims to determine the relationship between the level of ChatGPT utilisation as a learning medium and the Provisional Achievement Index (IPS) of students in the Islamic Education Study Programme (PAI) at UIN Sunan Ampel Surabaya (UINSA). The study uses a quantitative approach with a correlational method, involving as the research population. Data were collected through a questionnaire on ChatGPT utilisation and documentation of GPA scores. The results of this study are expected to provide an empirical picture of the extent to which the intensity and quality of ChatGPT usage contribute to students' academic achievement. These findings are expected to serve as a basis for educators and educational institutions in developing effective technology-based learning strategies, particularly in the context of Islamic Education.